P197 Evaluation of the clinical utility of the Becton Dickinson ProbeTec Qx (BDQ) Trichomonas vaginalis molecular detection test in two large, urban GU medicine services. (30th June 2016) - Tipple, Craig; Rayment, Michael; Rebec, Monica; Murray, John; Jones, Rachael; Wilkinson, Dawn
Abstract : Background: BASHH guidelines recommend molecular tests to aid diagnosis of Trichomonas vaginalis (TV), but many clinics use relatively insensitive techniques (pH, wet-prep microscopy (WPM) and culture). Objectives: To establish a laboratory pathway for TV testing with the BDQ assay, determine TV prevalence, and identify variables associated with TV detection. Methods: A prospective study of 900 women attending clinics for STI testing was undertaken. All were offered TV BDQ tests. Data collected: demographics, symptoms, results of near-patient tests and BDQ for TV, Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC). Women with any positive TV result were treated and invited to attend for test of cure (TOC). Data were collected in Excel and analysed in SPSS. Results: 891 women had a TV BDQ test. 472 (53%) were white, 143 (16%) black; median age 28yrs. 499 (55%) were symptomatic. Infections detected by BDQ: 11 TV (1.2%), 3 GC (0.3%) and 44 CT (4.9%). Of BDQ+ TV infections: 8 (73%) black, 7 (64%) symptomatic, 4/7 (57%) WPM+, 4/4 (100%) pH > 4.5, 7/7 (100%) Hay-Ison Grade 2, and 1/3 (33%) TV culture+. Mean BDQ turn-around time: 3.44 days. All received treatment. 9/9 (100%) were BDQ negative at TOC (mean time to TOC 15 days (range: 7–42). In univariate analysis, only black ethnicity was associated with likelihood of TV BDQ+ (RR 10.2 [95%CI 2.15–48.4]). Discussion: The use of the BDQ enhanced detection of TV in asymptomatic and symptomatic populations. Cost effective implementation of the test will rely upon further work to reliably detect demographic and clinical variables that predict positivity.